MLCC and MLCC preparation method for improving polarization crack of MLCC

By optimizing the batching and lamination steps in the MLCC production process, the problem of polarization cracking of the internal capacitor after sintering of NPO products is solved, and the product density and electrical performance are improved.

CN119811897AActive Publication Date: 2025-04-11XIAMEN HUAXINAN ELECTRONIC TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510021455.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

In the existing MLCC production process, polarization cracking inside the capacitor is prone to occur after sintering of NPO products, resulting in poor reliability of the product's capacitor and low capacity and withstand voltage.

Method used

The polarized cracking problem of MLCC is improved by optimizing the ingredients and lamination steps, including porcelain powder predispersion, two-step grinding, baking treatment and sandwich packaging.

Benefits of technology

It effectively improves the density and electrical performance of MLCC products, reduces polarization cracking, and improves the reliable performance of capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811897A_ABST
    Figure CN119811897A_ABST
Patent Text Reader

Abstract

The invention relates to the field of manufacturing of electronic components, in particular to an MLCC and an MLCC preparation method for improving polarization cracking of the MLCC. The preparation method provided by the invention comprises a burdening step and a laminating step, the material preparation step sequentially comprises the procedures of ceramic slurry pre-dispersion, first-step grinding and second-step grinding; wherein the ceramic slurry pre-dispersion process is carried out in a stirrer, and the first-step grinding process and the second-step grinding process are carried out in a sand mill. The laminating step sequentially comprises the procedures of baking, packaging, vacuumizing, laminating, cooling and unbagging; in the bar baking process, the unlaminated bars are placed at the temperature of 45-65 DEG C for bar baking treatment for 1-4 h; in the packaging process, the block is packaged and bagged by adopting a sandwich packaging method, and the structure of the sandwich packaging method sequentially comprises a metal laminated cover plate, the block and a metal laminated plate from top to bottom. The product diaphragm prepared by the scheme of the invention has no patterns, lines and holes, is good in compactness, and can effectively improve the problem of polarization cracking in the capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic component manufacturing, and in particular to an MLCC and an MLCC preparation method for improving MLCC polarization cracking. Background Art

[0002] Capacitors are important electronic components. They are containers for storing electric charge and have functions such as direct current isolation and alternating current transmission, resonance, filtering, bypassing, and coupling. MLCC (Multi-layer Ceramic Capacitors), also known as chip-type multilayer ceramic capacitors, are made by stacking ceramic dielectric diaphragms with printed electrodes (inner electrodes) in a staggered manner, sintering at high temperature once to form a ceramic chip, and then sealing a metal layer (outer electrode) at both ends of the chip to form a structure similar to a monolith, so it is also called a monolithic capacitor. According to temperature characteristics and materials, MLCC can be divided into NPO, X7R, etc.

[0003] The existing traditional MLCC production process includes ingredients, casting, screen printing, lamination, cutting, debinding, sintering, chamfering, end sealing, end burning, electroplating, testing, appearance, and taping. Among them, the existing lamination process includes bagging, vacuuming, lamination, cooling, and bagging. In the specific operation, the blocks are directly packaged and laminated without other treatment before lamination, and the final product has obvious polarization cracking.

[0004] Currently, both NPO products and X7R products are manufactured using the above-mentioned MLCC production process. However, the use of the above-mentioned traditional MLCC production process to manufacture NPO products (NPO capacitors are one of the most commonly used monolithic ceramic capacitors with temperature compensation characteristics) will cause some NPO products to have polarization cracking inside the capacitors after sintering, resulting in poor capacitor reliability, low capacity and withstand voltage, and other issues. Summary of the invention

[0005] In order to solve the problems of the prior art mentioned in the background technology, the present application provides a method for preparing MLCC for improving the polarization cracking of MLCC, and the technical solution thereof is as follows: The present application provides a method for preparing MLCC for improving polarization cracking of MLCC, which includes a batching step and a lamination step; The batching steps include porcelain slurry pre-dispersion, first step grinding, and second step grinding processes in sequence; wherein the porcelain slurry pre-dispersion process is carried out in a mixer, and the first step grinding process and the second step grinding process are carried out in a sand mill; The lamination step includes baking, packaging, vacuuming, lamination, cooling, and bagging processes in sequence; in the baking process, the unlaminated bar blocks are placed at 45-65°C for baking treatment for 1-4 hours; in the packaging process, the bar blocks are packaged and bagged using a sandwich packaging method, wherein the structure of the sandwich packaging method is, from top to bottom, a metal laminated cover plate, a bar block, and a metal laminate.

[0006] In some embodiments, in the baking process, the unlaminated blocks are placed at 55-60° C. for baking for 2 hours.

[0007] In some embodiments, the lamination step includes the steps of drying, packaging, vacuuming, laminating, cooling, and bagging in sequence, and the process is as follows: Baking: Place the unlaminated blocks at 45-65°C for 1-4 hours; Packaging: The bacon is packed and bagged by sandwich packing method, wherein the structure of the sandwich packing method is metal laminated cover plate, bacon, and metal laminate plate from top to bottom; Vacuuming: After the cubes are packed in bags, the bag mouth is heat-sealed and the air inside the bag is evacuated to seal the cubes; Lamination: Put the packaged blocks into the laminator for lamination; Cooling: The laminated blocks are cooled; Unpacking: Unpack the cooled blocks and collect the materials.

[0008] In some embodiments, the process of the batching step is: Pre-dispersion of porcelain slurry: Pre-disperse the porcelain powder and the solvent in a mixer to make them fully and evenly mixed to obtain porcelain slurry; First grinding step: placing the porcelain slurry in a sand mill for first grinding to obtain a first grinding slurry with a certain particle size range; The second grinding step: the first grinding slurry is stirred and mixed with a binder and a plasticizer to be uniform, and then a second grinding step is performed in a sand mill to obtain a second grinding slurry with a certain particle size range; Test and discharge: Test the parameters of the second polishing slurry and discharge it.

[0009] In some embodiments, in the ceramic slurry pre-dispersion process, the ceramic powder is MLC-320NB ceramic powder.

[0010] In some embodiments, the process of the batching step is: Pre-dispersion of porcelain slurry: Porcelain powder and solvent are put into a mixer and stirred to be pre-dispersed, so that the porcelain powder and solvent are fully mixed and uniform to obtain porcelain slurry; The first step of grinding: placing the porcelain slurry in the A tank of the sand mill, and grinding the porcelain slurry in the A tank and the B tank of the sand mill in a cycle to obtain a first grinding slurry with a certain particle size range; The second step of grinding: the first grinding slurry is stirred and mixed with the binder and the plasticizer to be uniform, and then the mixed slurry is cyclically ground in the A tank and the B tank of the sand mill to obtain the second grinding slurry with a certain particle size range; Testing and discharging: testing the density, viscosity and solid content parameters of the second grinding slurry, and discharging the material after the test is qualified; Wherein, the particle size of the first polishing slurry is (0.57-0.63) μm; the particle size of the second polishing slurry is (0.57-0.63) μm.

[0011] In some embodiments, the sand mill is a horizontal sand mill, and the grinding balls used in the first step of grinding and the second step of grinding are zirconium balls with a diameter of 0.5±0.03 mm.

[0012] In some embodiments, the metal laminate cover plate and the metal laminate plate are both aluminum plates.

[0013] In some embodiments, the preparation method includes the steps of batching, casting, screen printing, lamination, cutting, debinding, sintering, chamfering, end sealing, end burning, electroplating, testing, appearance, and braiding in sequence.

[0014] The present application provides an MLCC, which is manufactured using the MLCC manufacturing method for improving MLCC polarization splitting as described above.

[0015] Compared with the existing technology, this application has the following beneficial effects: The MLCC preparation method for improving MLCC polarization cracking provided in the present application has a product film without patterns, lines, or holes, has good density, and can effectively improve the problem of polarization cracking inside the capacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0017] Figure 1 A schematic flow chart of the lamination step in the preparation method provided in this application; Figure 2 A schematic diagram of a sandwich packaging method in the lamination step of the preparation method provided in the present application; Figure 3This is a physical picture of the surface of the cast film in Comparative Example 1; Figure 4 This is a physical picture of the surface of the cast film in Example 3; Figure 5 This is a physical picture of the MLCC product in Comparative Example 2; Figure 6 This is a physical picture of the MLCC product in Example 3. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0019] This application provides the following operation examples of the MLCC preparation method for improving MLCC polarization cracking: Step 1. Select materials: The ceramic powder used is MLC-320NB ceramic powder.

[0020] Step 2: Ingredients: The specific process is as follows: Pre-dispersion: The batching operation is carried out in a pre-dispersion mixer. The porcelain powder and solvent are put into the mixer and stirred for (50-80) minutes to fully mix the porcelain powder and the solvent. After the mixing is completed, the mixed slurry is pumped into the A tank of the sand mill using a diaphragm pump, and then the sand mill is turned on. The porcelain slurry is circulated and ground in the A tank and B tank of the sand mill to perform the first step of grinding (step A). ​​After the first step of grinding to a particle size within a suitable range, the binder and plasticizer are added, and the mixture is stirred and mixed for (30-60) minutes after the addition. After the binder and the porcelain slurry are fully mixed (the viscosity of the porcelain slurry is within a certain stable range), the sand mill is turned on. In the sand mill, the mixed slurry is circulated and ground in the A tank and B tank of the sand mill to perform slurry mixing and the second step of grinding (step B). Among them, the particle size of the first grinding slurry is (0.57-0.63) μm; the particle size of the second grinding slurry is (0.57-0.63) μm.

[0021] The second step is to grind until the particle size and other parameters are within the appropriate range, and then test the slurry density, viscosity, solid content and other parameters. After passing the test, the material can be discharged. Step 3: Casting, screen printing, lamination: The slurry discharged after the batching step is subjected to casting, screen printing and lamination operations, specifically: Casting: The ceramic slurry is evenly coated on the release film at a certain thickness, and then baked at a certain temperature to form a dry ceramic blank film; Printing electrodes: The internal electrode slurry is printed on the cast ceramic blank film (i.e., ceramic dielectric film) into an internal electrode pattern of a certain size and shape to obtain an electrode pattern dielectric film; Lamination: The printed electrode pattern dielectric film is stacked into the required MLCC Bar block (i.e., Bar block) according to a certain offset amount. Step 4, Lamination: like Figure 1 As shown, the lamination process is as follows: Baking: Place the unlaminated blocks in an oven at 45-65°C for 1-4 hours; Packaging: Figure 2 As shown, the sandwich packaging method is used to package the bar blocks and bag them, wherein the structure of the sandwich packaging method is, from top to bottom, an upper metal aluminum plate, a bar block, and a lower metal aluminum plate; vacuuming: after the bar block is bagged, the bag mouth is heat-sealed and the air in the bag is evacuated to seal the bar block; laminating: the packaged bar block is placed in a laminator for lamination; cooling: the laminar bar block is cooled; unpacking: the cooled bar block is unpacked and collected to complete the lamination step. Step 5, cutting, debinding, sintering, chamfering, end sealing, end burning, electroplating, testing, appearance, and taping steps: The laminated blocks are cut, debonded, sintered, chamfered, capped, burned, electroplated, tested, surface treated, and taped to obtain MLCC products. Specifically: Cutting: Cut the green body obtained after lamination into single green bodies according to a certain step distance to obtain ceramic green bodies; Glue removal: Heat the ceramic green body according to a certain temperature curve to remove the adhesive and other organic substances in the chip; Sintering: The ceramic chip is sintered at high temperature according to the temperature curve to give the chip a certain mechanical strength. Chamfering: According to the process requirements, the electrodes in the sintered ceramic chip are fully exposed through the chamfering machine; End sealing: Apply the end paste on the two ends of the exposed electrodes of the product, and seal the two ends to form the external electrode; End burning: Put the end-sealed product into a high-temperature furnace to burn the end, sinter the end electrode to make it in close contact with the electrode plate to form the initial body of the ceramic capacitor; Electroplating: Plate a metal layer on the electrode end of the initial body of the ceramic capacitor to form a finished ceramic capacitor; Appearance: Pick out the finished ceramic capacitor with surface defects; Testing: Test the electrical properties of the capacitor product (withstand voltage BV, capacitance Cp, loss DF and insulation resistance IR, etc.) and remove defective products; Taping: Pack the capacitor products according to size and quantity requirements. In order to verify the effect of the present application, the present application also provides the following embodiments and comparative examples: Example 1-3 (Preparation of NPO products) Step 1. Select materials: The ceramic powder used was MLC-320NB ceramic powder, the solvent used was a diluent (mixture of toluene and anhydrous ethanol in a weight ratio of 7:3), the adhesive used was LF02, the plasticizer used was DOP, and the dispersant used was AKM-0531.

[0022] The formula is: 60000g of porcelain powder, 30600g of adhesive, 2460g of plasticizer, 22380g of solvent, and 780g of dispersant.

[0023] Step 2: Ingredients: The specific process is as follows: Pre-dispersion: The batching operation is carried out in a pre-dispersion mixer. The ceramic powder and the solvent are put into the mixer and stirred for 60 minutes to fully mix the ceramic powder and the solvent. After the mixing is completed, the mixed slurry is pumped into the A tank of the horizontal sand mill using a diaphragm pump, and then the horizontal sand mill is turned on. The slurry circulates in the A tank and the B tank for many times to complete the first step of grinding (step A). ​​Among them, the grinding balls used in the first step of grinding are zirconium balls with a diameter of 0.5mm, and the ball-to-material weight ratio is 1:0.082. The particle size of the first grinding slurry obtained by grinding is 0.60±0.03μm. The grinding process is that the main engine speed of the horizontal sand mill is 30HZ, the pump speed is 30HZ, the stirring speed of tank A is 27HZ, the stirring speed of tank B is 27HZ, and tanks A and B are circulated back and forth 20 times (that is, the slurry is discharged from tank A to tank B after one cycle after being ground by the main engine, and then from tank B to tank A after being ground by the main engine, and so on, a total of 20 times).

[0024] After the first step of grinding to a suitable particle size, add adhesive and plasticizer to the slurry. After adding and mixing for 30 minutes, turn on the horizontal sand mill, and circulate the mixed slurry in the A tank and B tank of the sand mill to complete the slurry mixing and the second step of grinding (B step). Among them, the grinding balls used in the second step of grinding are zirconium balls with a diameter of 0.5mm, and the ball-to-material weight ratio is 1:0.060. The particle size of the first grinding slurry obtained by grinding is 0.60±0.03μm. The grinding process is that the main machine speed of the horizontal sand mill is 30HZ, the pump speed is 30HZ, the stirring speed of tank A is 27HZ, the stirring speed of tank B is 27HZ, and tank A and tank B are circulated back and forth 10 times (that is, the slurry is discharged from tank A to tank B after being ground by the main machine for one cycle, and then from tank B to tank A after being ground by the main machine, and then circulated back and forth, tank A to tank B is 1 time, tank B to tank A is 2 times, and so on, a total of 10 times).

[0025] The second step is to grind until the particle size and other parameters are within the appropriate range, and then test the slurry density, viscosity, solid content and other parameters. After passing the test, the material can be discharged. Step 3: Casting, screen printing, lamination: The slurry discharged after the batching step is subjected to casting, screen printing and lamination operations, specifically: Casting: The ceramic slurry is evenly coated on the release film at a certain thickness, and then baked at a certain temperature to form a dry ceramic blank film; Printing electrodes: The internal electrode slurry is printed on the cast ceramic blank film into an internal electrode pattern of a certain size and shape to obtain an electrode pattern dielectric film; Lamination: The printed electrode pattern dielectric film is stacked into the required MLCC Bar block (i.e., Bar block) according to a certain offset amount. Step 4, Lamination: The lamination process is as follows: Baking: Place the unlaminated blocks in an oven and bake them at a certain temperature. The specific baking temperatures of different experimental groups are shown in Table 1 below. Table 1

[0026] Packaging: The bars are packed in sandwich packaging and bagged, wherein the structure of the sandwich packaging method is upper metal plate, bar blocks, and lower metal plate from top to bottom; wherein the top laminated cover plate is an aluminum plate with Teflon-plated surface and a square shape with a side length of 153 mm; the middle layer is the pressed bar block product with a square shape of 155 mm; the bottom laminated plate is an aluminum plate with a galvanized surface and a square shape of 180 mm.

[0027] Vacuuming: After the bar blocks are bagged, the bag opening is heat-sealed and the air inside the bag is evacuated to seal the bar blocks; Lamination: The sealed bar blocks are placed in a laminator for lamination; wherein the lamination operation is performed according to a certain pressure curve, and the specific pressure curve is shown in Table 2 below.

[0028] Table 2

[0029] Cooling: Cool the laminated blocks; Unpacking: Unpack the cooled blocks and collect the materials to complete the lamination process. Step 5: Cutting, debinding, sintering, chamfering, end sealing, end burning, electroplating, testing, appearance, and taping: The laminated blocks are cut, debonded, sintered, chamfered, capped, burned, electroplated, tested, surface treated, and taped to obtain MLCC products. Specifically: Cutting: Cut the green body obtained after lamination into individual green bodies according to a certain step distance; Debinding: Heat the ceramic green body at a temperature of 250-300℃ to remove the adhesive and other organic substances in the chip; Sintering: Sinter the debinding product at a high temperature of 1270-1300℃ for 35-40 hours; Chamfering: According to the process requirements, the internal electrodes of the sintered ceramic chip are fully exposed through the chamfering machine; End sealing: Apply the end paste to the two ends of the exposed electrode of the product, and seal the two ends to form an external electrode; End firing: The end capping product is The product is placed in a high-temperature furnace for sintering, and the end electrode is sintered to make it in close contact with the electrode plate to form the initial body of the ceramic capacitor; electroplating: the electrode end of the initial body of the ceramic capacitor is plated with a metal layer to form the finished ceramic capacitor; appearance: the finished ceramic capacitor with surface defects is picked out; testing: the electrical performance of the capacitor product (withstand voltage BV, capacitance Cp, loss DF and insulation resistance IR, etc.) is tested, and defective products are removed; taping: the capacitor product is packaged according to the size and quantity requirements to complete the production of MLCC products. Comparative Example 1 (traditional batching process, the batching steps are different from the embodiment) The only difference from Example 3 is that the batching steps are different. The batching process of this comparative example is: The mixing and grinding operations from feeding to discharging are all carried out in the same ball mill, that is, the porcelain slurry pre-dispersion process, the first step grinding (step A) and the second step grinding (step B) of Example 3 are all carried out in the same ball mill.

[0030] Among them, the grinding balls used in the first step of grinding are two specifications of zirconium balls with diameters of 3mm and 5mm (weight ratio of 1:1), and the ball-to-material weight ratio is 1:5.68; the grinding process parameters are: the ball mill speed parameter is 45rpm, and the ball milling time parameter is 5 hours; the grinding balls used in the second step of grinding are two specifications of zirconium balls with diameters of 3mm and 5mm (weight ratio of 1:1), and the ball-to-material weight ratio is 1:4.6; the grinding process parameters are: the ball mill speed parameter is 45rpm, and the ball milling time parameter is 13 hours.

[0031] Other preparation processes and conditions are consistent with those in Example 3.

[0032] Comparative Example 2 (conventional lamination process, the lamination step is different from the embodiment) The only difference from Example 3 is that the lamination steps are different. The process flow of the lamination steps in this comparative example is packaging, vacuuming, lamination, cooling, and bagging. The blocks are not subjected to other treatments before lamination, but are directly packaged and then laminated. The specific process is: Packaging: Use the traditional sandwich packaging method to cover the upper and lower surfaces of the bar with PET film and then bag it; Vacuuming: same as in Example 3; Lamination: The packaged blocks are placed in a laminator and laminated according to a certain pressure curve. The lamination process is consistent with that in Example 3; Cooling: The laminated blocks are cooled in the same process as in Example 3; Unpacking: unpacking the cooled bar blocks and collecting the materials, the process is the same as that in Example 3; Other preparation processes and conditions are consistent with those in Example 3.

[0033] Comparative Example 3 (Raw material selection is different from that of the embodiment) The only difference from Example 3 is that the ceramic powder is FW-K30N ceramic powder. The other preparation processes and conditions are the same as those in Example 3.

[0034] The cast film and MLCC products of the embodiments and comparative examples were subjected to corresponding performance tests: The test results are shown in Table 3 below: Table 3

[0035] Analysis of the test data shows that: 1. Density of cast film surface: like Figure 3 As shown, the surface of the cast film of Comparative Example 1 has patterns, lines, holes, and poor density; Figure 4 As shown, the surface of the cast film of Example 3 has no patterns, lines, or holes, and has good density. The reasons are as follows: Comparative Example 1 adopts the existing batching process method, and the operations of mixing and grinding (step A + step B) from adding materials to discharging materials are all carried out in the same ball mill. This operation mode has the following problems: poor slurry dispersion effect and uneven particle size distribution: the ball mill is an old-fashioned machine, and the zirconium balls used are larger in size (3-5mm), which will result in poor slurry grinding and dispersion effects, uneven particle distribution, etc., resulting in poor dispersion of the cast film, and the film has patterns, lines, holes and poor density.

[0036] The embodiment optimizes the batching steps, selects appropriate specific porcelain powder and coordinates it with the optimized and adjusted batching process, so that the porcelain slurry is ground into a uniform particle size and has good dispersibility, so that the surface of the cast film has no patterns, lines, holes, and good density.

[0037] 2. Polarization cracking of MLCC products From the data and Figure 5-6 It can be seen that compared with Example 3, Figure 5 As shown, the comparative example 2 using the conventional lamination step exhibits obvious polarization cracking. Moreover, compared with the embodiment 3, the comparative example 3 also exhibits obvious polarization cracking. Figure 6 As shown, Example 3 has no polarization splitting phenomenon.

[0038] The MLCC preparation method for improving MLCC polarization cracking optimized in this application can significantly improve polarization cracking by selecting ceramic powder materials and coordinating the batching steps and lamination steps after optimization and adjustment. The reasons are analyzed as follows: First, the existing lamination process is bagging, vacuuming, laminating, cooling, and unpacking. The blocks are not processed before lamination, but are directly packaged and laminated. The blocks are laminated without other treatments, resulting in large stress in the blocks due to the temperature and pressure in the laminator during the lamination process. After the subsequent debinding and sintering processes, obvious polarization cracking was found after destructive physical analysis (DPA).

[0039] The improved lamination process of the present application is baking, bagging (sandwich packaging method with metal plates pressed together), vacuuming, lamination, cooling, and unpacking. The original direct lamination is changed to placing the bar blocks in an oven for baking before lamination, and the baking conditions are optimized to form specific process conditions. Among them, the unlaminated bar blocks are placed in an oven for baking, so that the inside of the bar blocks are heated and slight stress is generated, so as to achieve the purpose of preliminary softening of the bar blocks, solve the polarization cracking phenomenon caused by rapid extrusion during the lamination process, and improve the reliability of capacitor products. In addition, the traditional sandwich packaging process uses PET film to cover the surface of the bar blocks. The PET film is relatively soft, and after lamination, the bar blocks will be stretched and deformed to a large extent. The lamination step of the present application is changed from PET film to metal plate, so that the bar blocks are less stretched and deformed after lamination, and the metal plate can be reused.

[0040] Secondly, ceramic powder is the main material of capacitors, and different ceramic powders have an impact on polarization cracking. Therefore, in order to improve polarization cracking, it is necessary to select suitable ceramic powder and the corresponding preparation process. The existing NPO products use FW-K30N ceramic powder. After verification, it was found that when FW-K30N ceramic powder was used, the improvement of polarization cracking phenomenon was not good. This application uses a specific MLC-320NB ceramic powder in combination with an optimized preparation process. The ceramic powder ingredients have good dispersion effect and uniform particle distribution. The electrical performance and reliability of the obtained products meet the technical requirements.

[0041] In addition, the present application further optimizes the baking process parameters. From the data in Table 2, it can be seen that baking for 2 hours at a process condition of 55°C is the best choice, which has the best effect on improving the polarization cracking of MLCC.

[0042] In summary, compared with the prior art, the MLCC preparation method for improving MLCC polarization cracking provided by the present application has the following design concepts and effects: The polarization cracking phenomenon exists in NPO material capacitors under the existing production process. The MLCC preparation method for improving MLCC polarization cracking provided in this application can effectively solve the polarization cracking problem that occurs inside the capacitor under the traditional preparation process.

[0043] The production process of MLCC includes: batching - casting - screen printing - lamination - lamination - cutting - debinding - sintering - chamfering - end sealing - sintering - electroplating - testing - appearance - taping. This application mainly improves polarization cracking by specific selection of raw materials, optimizing and adjusting batching steps, and optimizing and adjusting lamination steps. It is mainly divided into three parts: selecting ceramic powder, adjusting batching steps, and adjusting lamination steps, as follows: 1. Select porcelain powder Ceramic powder is the main material of capacitors, and different ceramic powders have an impact on polarization cracking. Therefore, in order to improve polarization cracking, it is necessary to select appropriate ceramic powder and adapt it to the corresponding preparation process.

[0044] Existing NPO products use FW-K30N porcelain powder. After verification, it was found that the improvement of polarization cracking phenomenon was not good when FW-K30N porcelain powder was used. This application uses a specific MLC-320NB porcelain powder in combination with an optimized preparation process. The porcelain powder has a good dispersion effect and uniform particle distribution. The electrical performance and reliability of the product meet the technical requirements.

[0045] 2. Adjust the batching process In the existing batching process, all operations from adding materials to discharging materials, mixing and grinding (step A + step B) are carried out in the same ball mill. This operation mode has the following problems: poor slurry dispersion effect and uneven particle size distribution: As an old-fashioned machine, the ball mill uses larger zirconium balls (3-5mm), which will result in poor slurry grinding and dispersion effects, uneven particle distribution, etc., resulting in poor dispersion of cast film, patterns, lines, holes and poor density of the film.

[0046] This application optimizes the batching steps, performs pre-dispersion independently in a mixer, adjusts the grinding in a ball mill to two steps in a horizontal sand mill, and adjusts the corresponding ball mill size. The grinding process A / B tanks are cycled to make the slurry dispersible and uniform in particle size. By selecting appropriate specific porcelain powders and coordinating with the optimized batching process, the porcelain slurry is ground to a uniform and dispersible particle size, so that the surface of the cast film has no patterns, lines, or holes, and has good density.

[0047] 3 Adjust the lamination steps: The existing lamination process is bagging, vacuuming, laminating, cooling, and unpacking. The blocks are not processed before lamination, but are directly packaged and laminated. If the blocks are directly laminated without other treatment, the blocks will be affected by the temperature and pressure in the laminator during the lamination process, resulting in large stress on the blocks. After the subsequent debinding and sintering processes, polarization cracking was found after destructive physical analysis (DPA).

[0048] The improved process flow of the lamination steps in the present application is baking, bagging (sandwich bag method of metal plate pressing), vacuuming, laminating, cooling, and bagging.

[0049] The original direct lamination was changed to placing the blocks in an oven for baking before lamination, and the baking conditions were optimized to form specific process conditions. Among them, the unlaminated blocks were placed in the oven for baking, so that the inside of the blocks was heated and slight stress was generated, achieving the purpose of preliminary softening of the blocks, solving the polarization cracking phenomenon caused by rapid extrusion during the lamination process, and improving the reliability of capacitor products.

[0050] In addition, the packaging process is also adjusted: the traditional sandwich packaging process uses PET film to cover the surface of the bar block. The PET film is relatively soft, and after lamination, the bar block will be stretched and deformed significantly. The lamination step of the present application is changed from PET film to metal plate, so that the bar block is less stretched and deformed after lamination, and the metal plate can be reused.

[0051] In addition, the present application further optimizes the baking process parameters, and baking for 2 hours at 55°C is the best choice. Under this process condition, the improvement of MLCC polarization cracking is best.

[0052] In summary, the present application achieves a product film without patterns, lines, or holes, with good density, and can effectively improve the polarization cracking problem of the product through the specific selection of raw materials, optimization and adjustment of the batching steps, and optimization and adjustment of the lamination steps.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing MLCC for improving polarization cracking of MLCC, characterized in that: The method comprises a batching step and a laminating step; The batching steps include porcelain slurry pre-dispersion, first step grinding, and second step grinding processes in sequence; wherein the porcelain slurry pre-dispersion process is carried out in a mixer, and the first step grinding process and the second step grinding process are carried out in a sand mill; The lamination step includes baking, packaging, vacuuming, lamination, cooling, and bagging processes in sequence; in the baking process, the unlaminated bar blocks are placed at 45-65°C for baking treatment for 1-4 hours; in the packaging process, the bar blocks are packaged and bagged using a sandwich packaging method, wherein the structure of the sandwich packaging method is, from top to bottom, a metal laminated cover plate, a bar block, and a metal laminate.

2. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 1, characterized in that: In the baking process, the unlaminated blocks are placed at 55-60° C. for baking for 2 hours.

3. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 1, characterized in that: The lamination step includes the following steps: baking, packaging, vacuuming, laminating, cooling, and bag unpacking. Baking: Place the unlaminated blocks at 45-65°C for 1-4 hours; Packaging: The bacon is packed and bagged by sandwich packing method, wherein the structure of the sandwich packing method is metal laminated cover plate, bacon, and metal laminate plate from top to bottom; Vacuuming: After the cubes are packed in bags, the bag mouth is heat-sealed and the air inside the bag is evacuated to seal the cubes; Lamination: Put the packaged blocks into the laminator for lamination; Cooling: The laminated blocks are cooled; Unpacking: Unpack the cooled blocks and collect the materials.

4. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 1, characterized in that: The process of the batching step is: Pre-dispersion of porcelain slurry: Pre-disperse the porcelain powder and the solvent in a mixer to make them fully and evenly mixed to obtain porcelain slurry; First grinding step: placing the porcelain slurry in a sand mill for first grinding to obtain a first grinding slurry with a certain particle size range; The second grinding step: the first grinding slurry is stirred and mixed with a binder and a plasticizer to be uniform, and then a second grinding step is performed in a sand mill to obtain a second grinding slurry with a certain particle size range; Test discharge: Test the parameters of the second polishing slurry and discharge it.

5. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 4, characterized in that: In the porcelain slurry pre-dispersion process, the porcelain powder adopts MLC-320NB porcelain powder.

6. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 1, characterized in that: The process of the batching step is: Pre-dispersion of porcelain slurry: Porcelain powder and solvent are put into a mixer and stirred to be pre-dispersed, so that the porcelain powder and solvent are fully mixed and uniform to obtain porcelain slurry; The first step of grinding: placing the porcelain slurry in the A tank of the sand mill, and cyclically grinding the porcelain slurry in the A tank and the B tank of the sand mill to obtain a first grinding slurry with a certain particle size range; The second step of grinding: the first grinding slurry is stirred and mixed with the binder and the plasticizer to be uniform, and then the mixed slurry is cyclically ground in the A tank and the B tank of the sand mill to obtain the second grinding slurry with a certain particle size range; Testing and discharging: testing the density, viscosity and solid content parameters of the second grinding slurry, and discharging the material after the test is qualified; Wherein, the particle size of the first polishing slurry is (0.57-0.63) μm; the particle size of the second polishing slurry is (0.57-0.63) μm.

7. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 4, characterized in that: The sand mill is a horizontal sand mill, and the grinding balls used in the first step of grinding and the second step of grinding are zirconium balls with a diameter of 0.5±0.03 mm.

8. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 1, characterized in that: The metal laminate cover plate and the metal laminate plate are both aluminum plates.

9. The method for preparing MLCC for improving polarization cracking of MLCC according to claim 1, characterized in that: The steps include batching, casting, screen printing, lamination, cutting, debinding, sintering, chamfering, end sealing, end burning, electroplating, testing, appearance and taping.

10. An MLCC, characterized in that: The MLCC is prepared by the MLCC preparation method for improving MLCC polarization splitting as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-frequency high-Q-value chip-type multiplayer ceramic capacitor

    CN102394175A

  • Packaging process and packaging assembly for ceramic element bar block lamination

    CN112660610A

  • Cutting and glue discharging process of chip type high-capacity multilayer ceramic capacitor

    CN115572171A

  • Lamination process of chip type high-capacity multilayer ceramic capacitor block

    CN115700897A

  • Multilayer chip ceramic capacitor and preparation method thereof

    CN116612990A